2010
DOI: 10.1016/j.jiph.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and the long-distance truck drivers in south-west Nigeria: A cross-sectional survey on the knowledge, attitude, risk behaviour and beliefs of truckers

Abstract: Although the HIV prevalence rate observed among the tested participants (2.4%) was lower than the overall national prevalence (4.6%), the result calls for concern as it showed that the population of truckers is a potential high risk group in Nigeria. Also, the mobile nature of this high-risk group has made getting HIV/AIDS awareness messages across to them a difficult task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 10 publications
4
34
3
Order By: Relevance
“…In each study locations, effort was made to include all PLWHA (who gave their consents) in the study. Also, while we recognized that interviewing all PLWHA in the various locations would have yielded a more complete study, ethical considerations provide that participation in a study of this nature has to be by choice [19][20][21]28] and hence, this report covers Table 5 Results of the logistic regression for factors associated with variables describing anti-retroviral therapy adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each study locations, effort was made to include all PLWHA (who gave their consents) in the study. Also, while we recognized that interviewing all PLWHA in the various locations would have yielded a more complete study, ethical considerations provide that participation in a study of this nature has to be by choice [19][20][21]28] and hence, this report covers Table 5 Results of the logistic regression for factors associated with variables describing anti-retroviral therapy adoption.…”
Section: Discussionmentioning
confidence: 99%
“…These further substantiated the fact that HIV/AIDS is really an epidemic majorly among the active age group. Past studies conducted among PLWHA revealed that the epidemic is more prevalent among young adult [2,15,20,22,28,29].…”
Section: Factorsmentioning
confidence: 99%
“…Healthcare workers also have been identified as people on occupational risk of HIV transmission as most patients are unaware of their HIV status or do not want to disclose it leading professionals such as nurses to treat them as noninfected persons (Tesfay & Habtewold, 2014;Mashoto et al, 2013;Alemie, 2012). Evidence from surveys conducted in Botswana, Mozambique, Malawi, Nigeria, and South Africa have confirmed the HIV dispersers' label of long-distance truck drivers in Sub-Saharan Africa, who engage consistently in irresponsible and highly risky sexual behaviours (Atilola et al, 2010;Kribs-Zaleta et al, 2005). Similarly, companies operating in the mining sector in the DR Congo like in other African countries experienced the hit of HIV/AIDS towards the vulnerabilities to the virus displayed by miners (Stroebel & Mavard, 2008, p. 14).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Determine ® and Starpac ® test kits were used as recommended by the National Agency for the Control of AIDS (NACA). Determine ® was used for the screening while Starpac ® was used for confirmation of positive results [15]. Testing was conducted by certified medical staff from the Redeemed Action Packed AIDS Committee (RAPAC) -a faith based HIV/AIDS NGO.…”
Section: Sample Collection and Hiv Testmentioning
confidence: 99%
“…Testing was conducted by certified medical staff from the Redeemed Action Packed AIDS Committee (RAPAC) -a faith based HIV/AIDS NGO. In addition, participants were requested to fill an additional (but very brief) questionnaire containing questions on the age of the participants and selected risk behaviours [15]. Free counselling was conducted for as many as agreed to be counseled.…”
Section: Sample Collection and Hiv Testmentioning
confidence: 99%